Impact of air stagging in furnace on processes in power steam boiler TPP Kostolac B - Stupar Goran M. (Tehnika, 2021)
The European normatives prescribe the maximum content of 200 mg/Nm3 in dry flue gases with oxygen content of 6% for existing pulverized coal-fired power plants. In order to analyse the effects of applying some of the primary measures for NOx reduction on the overall steam boiler operation, calculational coupling of differential mathematical models has been applied. This calculation system enables reliable prediction of the performance of power steam boilers also in substoichiometric conditions, and the quality of the boiler operation can be described from the perspective of its effective, efficient, safe and ecological operation. In accorrdance to that, calculations of the steam boiler unit 1 TE Kostolac B have been carried out for the existing and the air staging combustion system. This paper presents an analysis of the influence of various parameters on the operation of the steam boiler with the application of primary measures.